Fala traqueoesofágica em laringectomizados totais: expressividade como proposta de intervenção - Medeiros, Niele Caroline Vasconcelos (2008)
Introduction: Tracheoesophageal speech obtained by means of a tracheoesophageal prosthesis has limitations, represented by its restricted melodic variation and intensity. Thus, there is interference in the communicative efficiency of these individuals. The speech therapist in the context of total laryngectomy has focused his/her work more in the direction of phonation. Frequently, by giving more attention to the voice, the therapist forgets the other aspects of verbal (speed of speech, emphasis, pause and inflection, among others) and non-verbal (posture, gestures and facial expression) communication. Aim: to analyze expressiveness before and after completing a phonoaudiological intervention program, in two individuals with tracheoesophageal speech. Method: two subjects (S1 and S2) with tracheoesophageal speech participated in a phonoaudiological program with focus on expressiveness, conducted in four meetings of two hours each. Two video recordings were made (one pre- and one post-intervention). Ten judges participated in the judgment of each subject s communication (the subject him/herself, three relatives, three phonoaudiologists experienced in attending oncologic patients, and three individuals from the population not familiar with tracheoesophageal speech. The judges were asked whether the communicative performance (in the two video recordings) was equal or different. If they perceived differences, they should justify their reply, identifying which aspect had changed, according to a pre-established evaluation script, with aspects of verbal and non-verbal communication. Results: In the opinion of S1, there were changes as regards facial expression, understanding and speed of speech, use of pauses and voice quality. S2 described the changes in a positive manner for the other aspects: bodily posture; head movements; facial expression, understanding and speed of speech, use of pauses and emphasis; voice intensity and quality. For the subjects relatives, the aspects most pointed out were: facial expression, understanding the speech and voice quality. The speech therapist made a more technical assessment of the verbal communication such as marking emphasis by pauses and variation in loudness, and they also associated more melodious speech with improvement in voice quality, although they made little mention of the non-verbal communication. The lay judges took more notice of the body when they perceived differences particularly in the gestures and facial expression, in addition to the improvements in understanding the speech and voice quality. Conclusion: In the perception of all the judges, verbal communication, so highly valued in the speech therapist clinic, received greater emphasis in totally laryngectomized individuals with tracheoesophageal speech, than non-verbal communication. The speech therapists were shown to identify changes in verbal communication in greater detail, and the lay judges observed communication from more overall aspect. This evidences that the speech therapist clinic is able to transcend the voice and place value on the work with expressiveness in the rehabilitation of these individuals